Psychological health, wellbeing and COVID-19: Comparing previously infected and non-infected South African employees - Hill, Carin (Frontiers in Psychology, 2022)
Most Covid-19 and work-related well-being research is centred around the adverse effects on employees’ psychological well-being and is not focused on the work-related well-being of those infected by SARS-CoV-2. Furthermore, Covid-19 and work-related well-being research is generally aimed at healthcare workers. The current study focused on investigating the difference in the level of burnout, anxiety, depression and stress between previously infected and uninfected participants. This study used a cross-sectional survey design and non-probability quota sampling to collect data. A retrospective pre-post design was used to determine the difference between the level of burnout of the participants before and after infection. Working adults in South Africa were targeted and divided into those previously infected (n = 245) and those not yet infected with Covid-19 (n = 221). Participants completed questionnaires relating to burnout, depression, anxiety, and stress. A comparison of means revealed a significant increase in burnout after being infected. Infected participants had significantly higher burnout, anxiety, depression, and stress levels than their non-infected counterparts. Emotional exhaustion, withdrawal, and stress were the most prevalent psychological ill-health problems. The results of this study indicated that a SARS-CoV-2 infection has a detrimental impact on participants’ psychological well-being and mental health compared to their own initially reported levels of burnout before infection, as well as compared to the levels of burnout, depression, anxiety and depression of the non-infected participants. Based on the findings, specific recommendations to industrial psychologists were made to manage the psychological impact of Covid-19 on employees.